Spatial and temporal pattern of road accidents and casualties in peninsular Malaysia - Shahid, Shamsuddin (Penerbit UTM Press, 2015)
Road traffic accidents are often found to follow some spatial and temporal patterns as the factors that influence road accident changes with space and time. Knowledge on spatial and temporal variability of accident can be helpful for optimizing resources in order to improve traffic security management. The objective of the present study is to assess the spatial and temporal variation in the incidence of road traffic accidents and casualties across the states of peninsular Malaysia. Recent trends in number of accidents, casualties and fatalities are also accessed using non-parametric statistical method. The results show more accidents but lower fatalities in more urbanized and developed states, and lower accident levels but more serious fatalities in less urbanized or developed states of Peninsular Malaysia. Trend analysis reveals increasing number of accidents, but decreasing number casualties in recent years in most of the states of Peninsular Malaysia. The temporal analysis shows clear seasonal pattern in accident in some states of Malaysia. Most of the accidents are found to occur in festive month of Hari Raya Puasa festival followed by the month of mid-year school holiday. It is expected that the finding of the study will help in making recommendations in order to improve road safety and reduce road traffic accident in Malaysia.